Normal human brainstem development in vivo: a quantitative fetal MRI study. (6th July 2021) - Dovjak, G. O.; Schmidbauer, V.; Brugger, P. C.; Gruber, G. M.; Diogo, M.; Glatter, S.; Weber, M.; Ulm, B.; Prayer, D.; Kasprian, G. J.
ABSTRACT: Objectives: To characterize spatiotemporal growth differences of prenatal brainstem substructures and cerebellum, using linear biometry and planimetry on fetal magnetic resonance imaging (MRI). Methods: In this retrospective study, we included fetuses with normal brain and a precise midsagittal T2‐weighted brain MRI sequence obtained between May 2003 and April 2019. The cross‐sectional area, rostrocaudal diameter and anteroposterior diameter of the midbrain, pons (basis pontis and pontine tegmentum), medulla oblongata and cerebellar vermis, as well as the transverse cerebellar diameter, were quantified by a single observer. The diameters were also assessed by a second observer to test inter‐rater variability. Results: We included 161 fetuses with normal brain and a precise midsagittal MRI sequence, examined at a mean ± SD gestational age of 25.7 ± 5.4 (range, 14 + 0 to 39 + 2) weeks. All substructures of the fetal brainstem and the cerebellum could be measured consistently (mean ± SD interobserver intraclass correlation coefficient, 0.933 ± 0.065). We provide reference data for diameters and areas of the brainstem and cerebellum in the second and third trimesters. There was a significant quadratic relationship between vermian area and gestational age, and all other measured parameters showed a significant linear growth pattern within the observed period ( P < 0.001). A significant change in the relative proportions of the brainstem substructures occurred between the beginning of the second trimester and the end of the third trimester, with an increase in the area of the pons ( P < 0.001) and a decrease in that of the midbrain ( P < 0.001), relative to the total brainstem area. Conclusions: The substructures of the fetal brainstem follow a distinct spatiotemporal growth pattern, characterized by a relative increase in the pons and decrease in the midbrain, between 15 and 40 weeks of gestation. Caution is needed when interpreting fetal brainstem appearance during the early second trimester, as the brainstem proportions differ significantly from the adult morphology. The reference data provided herein should help to increase diagnostic accuracy in detecting disorders of defective hindbrain segmentation. © 2020 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of International Society of Ultrasound in Obstetrics and Gynecology.